2012
DOI: 10.1007/s11682-012-9178-z
|View full text |Cite
|
Sign up to set email alerts
|

A functional MRI study of multimodal selective attention following mild traumatic brain injury

Abstract: Previous work suggests that the ability to selectively attend to and resolve conflicting information may be the most enduring cognitive deficit following mild traumatic brain injury (mTBI). The current study used fMRI to evaluate potential differences in hemodynamic activation in 22 mTBI patients and 22 carefully matched healthy controls (HC) during a multimodal selective attention task (numeric Stroop). Behavioral data indicated faster reaction times for congruent versus incongruent trials and for stimuli pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 64 publications
4
50
0
Order By: Relevance
“…Failure to properly modulate the DMN during cognitive tasks that require rapid shifting of attention and inhibition has also been observed in other studies with TBI cases. [58][59][60][61] For the five mTBI participants in the present study who entered with below-average Stroop inhibition switching scores, but who also improved by at least + 1 to + 4.5 SD post-LED, it is possible that nodes within the SN and/or the DMN were impacted post-LED, thus improving function and/or connections among these nodes. It is also possible that the red/NIR photons affected the DLPFC as well as the anterior cingulate cortex (ACC), both of which have been shown to be active during functional imaging studies of the Stroop effect.…”
Section: Executive Functionmentioning
confidence: 86%
“…Failure to properly modulate the DMN during cognitive tasks that require rapid shifting of attention and inhibition has also been observed in other studies with TBI cases. [58][59][60][61] For the five mTBI participants in the present study who entered with below-average Stroop inhibition switching scores, but who also improved by at least + 1 to + 4.5 SD post-LED, it is possible that nodes within the SN and/or the DMN were impacted post-LED, thus improving function and/or connections among these nodes. It is also possible that the red/NIR photons affected the DLPFC as well as the anterior cingulate cortex (ACC), both of which have been shown to be active during functional imaging studies of the Stroop effect.…”
Section: Executive Functionmentioning
confidence: 86%
“…Of note, 24 of the patients with mTBI presented in the current study are independent from our two previous publications examining evoked BOLD responses. 18,46 Inclusion criteria for the current study were based on the American Congress of Rehabilitation Medicine and included a Glasgow Coma Scale score of 13-15 (at presentation in the emergency department), loss of consciousness (if present) limited to 30 min, and post-traumatic amnesia limited to a 24-h period. 3 All patients with mTBI experienced a closed head injury resulting in an alteration in mental status at minimum (see online Supplementary Table 1 at ftp.liebertpub.com).…”
Section: Participantsmentioning
confidence: 99%
“…[9][10][11] Previous fMRI studies have reported a mixed pattern of both hypoand hyperactivation during the semi-acute stage of mTBI, as well as no observable group differences. [12][13][14][15][16][17][18][19][20] During normal neurovascular coupling, the blood oxygen level dependent (BOLD) response represents an amalgamation of signals derived from the ratio of oxy-to deoxyhemoglobin (primary), cerebral blood flow (CBF), and cerebral blood volume (CBV). [21][22][23] Although the exact nature of neurovascular coupling is still being investigated, the BOLD response likely results from the glutamatergic signaling after excitatory neurotransmission and/or underlying increased metabolic demands.…”
mentioning
confidence: 99%
“…There is evidence that alpha phase dynamics play a direct role in visual attention, and connectivity in the alpha band is required for higher order cognitive processing and consciousness (for a review, see Palva and Palva56, 57). Furthermore, an fMRI study of top‐down allocation of visual attention found that hemodynamic activations in healthy controls showed robust patterns of task‐related activations in bilateral dorsolateral prefrontal cortices and bilateral visual streams 19. Our findings suggest that the mTBI group were unable to boost long‐range alpha connectivity between occipital and frontal regions, possibly affecting their ability to appropriately allocate visual attention.…”
Section: Discussionmentioning
confidence: 71%
“…It is thought that these kinds of injury result in a disconnection within and between brain areas that is manifested as a loss or reduction of cognitive function 14, 15, 16. Functional connectivity studies acquired in the functional magnetic resonance imaging (fMRI) using a resting state paradigm in patients with mTBI report abnormalities in brain networks that include visual processing, limbic, motor, and cognitive functions,17 default mode function,18 default mode regulation,19 and aberrant connectivity in thalamo‐cortical networks that correlated with neurocognitive function and clinical symptomatology 20…”
Section: Introductionmentioning
confidence: 99%